THE EFFECTIVENESS OF USING SONGS IN TEACHING LISTENING SKILL AT THE SECOND GRADE OF SMP N 11 KABUPATEN SORONG - Nurteteng, Nurteteng; Sudibyo, Doni; Kolin, Karolina Feni (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
The use of song in the classroom can stimulate very positive associations to the study of a language. They can also make the classroom situation more enjoyable for students and increase the students’ interest to learn. Songs are chosen here because many of the students had listened to it. It can stimulate their motivation to learn, and to help the students learn English especially Listening Skill.The problem of this research can be stated how is using song effective in teaching listening skill at the second grade of SMP N 11 Kabupaten Sorong. The objectives of this study is to know effective or not using song in teaching listening skill at second grade of SMP N 11 Kabupaten Sorong. The study was conducted at SMP N 11 Kabupaten Sorong. The subjects of this study were the students at the second grade of SMP N 11 Kabupaten Sorong in two classes thus were as experimental and control groups. The numbers of the subjects were 24 students in experimental class (10 male and 12 female) and 24 students in control class (14 male and 10 female). This research used experimental method. The techniques of data collection used by the researcher are observation, and test (pre-test and post-test).Based on the statistical data, the researcher got a description that the results of test score of the experimental class which was given treatment using songs as media was 74.583 and control class which did not get treatment using songs as media that was 62.917. Based on the t-test with standard of significant 5%, it was found = 3.213 with t-table= 2.021 Consequently based the result, the process of learning Listening using songs as media is effective. In conclusion, there is a real difference in score between those who using song as media and those who learn without using songs as media. In another word, the process of learning Listening using songs as media is effective.